Bishops and the Provision of Homilies, 1520 to 1547 - Wabuda, Susan (The sixteenth century journal, 1994)
This article concerns the efforts of English bishops to ensure that their clergy, especially those with little learning, had material from which to read or preach in the pulpit. It shows that there was a measure of continuity between late medieval and Reformation practice in that responsible bishops were continually interested in setting forth orthodoxy, the encouragement of virtue, and the suppression of vice. In particular, bishops John Fisher of Rochester, John Longland of Lincoln, and John Stokesley of London printed their sermons, or they authorized important preaching material. This essay also examines Archbishop Thomas Cranmer's endeavors to issue his first Book of Homilies. Perceptions of what constituted orthodoxy were changing. He wished to replace traditional homilies, which often featured pious stories about the saints and their miracles, with new material based upon scripture. The shift to scripturally based homilies was an important innovation.